2023
DOI: 10.1128/aac.01188-22
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profiling of a Brugia malayi Muscarinic Acetylcholine Receptor as a Putative Antiparasitic Target

Abstract: The diversification of anthelmintic targets and mechanisms of action will help ensure the sustainable control of nematode infections in response to the growing threat of drug resistance. G protein-coupled receptors (GPCRs) are established drug targets in human medicine but remain unexploited as anthelmintic substrates despite their important roles in nematode neuromuscular and physiological processes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 129 publications
1
4
0
Order By: Relevance
“…This finding is in agreement with previous studies of C. elegans GAR-1, -2 and -3 and B. malayi GAR-2 and -3 that were also confirmed to be expressed throughout the entire life cycle ( Lee et al, 1999 , Lee et al, 2000 ; Gallo et al, 2023 ). In case of B. malayi the authors observed that GAR-3 mRNA is much highly abundant over the life cycle than in GAR-2, likely reflecting the acute physiological needs of the nematode ( Gallo et al, 2023 ). At this point it would be plausible to investigate if the GARs expression possesses the same feature across different nematode species.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is in agreement with previous studies of C. elegans GAR-1, -2 and -3 and B. malayi GAR-2 and -3 that were also confirmed to be expressed throughout the entire life cycle ( Lee et al, 1999 , Lee et al, 2000 ; Gallo et al, 2023 ). In case of B. malayi the authors observed that GAR-3 mRNA is much highly abundant over the life cycle than in GAR-2, likely reflecting the acute physiological needs of the nematode ( Gallo et al, 2023 ). At this point it would be plausible to investigate if the GARs expression possesses the same feature across different nematode species.…”
Section: Resultssupporting
confidence: 93%
“…C. elegans ’ GAR-3 regulates pharyngeal contractions ( Steger and Avery, 2004 ) and is also expressed in protractor muscles, as well as spicule-associated SPC and PCB cholinergic neurons ( Liu et al, 2007 ). GAR-3 in Brugia malayi has been found to be expressed in body wall muscle and neurons, as well as digestive and reproductive tissues, largely matching GAR-3 expression in C. elegans ( Gallo et al, 2023 ). Thus, it appears that GARs regulate many physiological functions of nematodes, some of which might be conserved across different taxa of this phylum.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations